Antioxidant Phytochemicals in Fresh Produce: Exploitation of Genotype Variation and Advancements in Analytical Protocols - Manganaris, George A.; Goulas, Vlasios; Mellidou, Ifigeneia; Drogoudi, Pavlina (Frontiers in Chemistry, 2018)
Horticultural commodities (fruit and vegetables) are the major dietary source of several bioactive compounds of high nutraceutical value for humans, including polyphenols, carotenoids and vitamins. The aim of the current review was dual. Firstly, towards the eventual enhancement of horticultural crops with bio-functional compounds, the natural genetic variation in antioxidants found in different species and cultivar/genotypes is underlined. Notably, some landraces and/or traditional cultivars have been characterized by substantially higher phytochemical content, i.e. small tomato of Santorini island (cv. ‘Tomataki Santorinis’) possesses appreciably high amounts of ascorbic acid. The systematic screening of key bioactive compounds in a wide range of germplasm for the identification of promising genotypes and the restoration of key gene fractions from wild species and landraces may help in reducing the loss of agro-biodiversity, creating a healthier ‘gene pool’ as the basis of future adaptation. Towards this direction, large scale comparative studies in different cultivars/genotypes of a given species provide useful insights about the ones of higher nutritional value. Secondly, the advancements in the employment of analytical techniques to determine the antioxidant potential through a convenient, easy and fast way are outlined. Such analytical techniques include electron paramagnetic resonance (EPR) and infrared (IR) spectroscopy, electrochemical and chemometric methods, flow injection analysis (FIA), optical sensors and high resolution screening (HRS). Taking into consideration that fruits and vegetables are complex mixtures of water- and lipid-soluble antioxidants, the exploitation of chemometrics to develop “omics” platforms (i.e. metabolomics, foodomics) is a promising tool for researchers to decode and/or predict antioxidant activity of fresh produce. For industry, the use of cheap and rapid optical sensors and IR spectroscopy is recommended to estimate the antioxidant activity, hence legislation does not allow its correlation with health claims.